THE RELATION BETWEEN RISK AND PROTECTIVE FACTORS FOR PROBLEM BEHAVIORS AND DEPRESSIVE SYMPTOMS, ANTISOCIAL BEHAVIOR, AND ALCOHOL USE IN ADOLESCENCE. Issue 5 (July 2014) - Monahan, Kathryn C.; Oesterle, Sabrina; Rhew, Isaac; Hawkins, J. David
<x xml:space="preserve">Abstract</x> Both externalizing and internalizing psychopathology increase throughout adolescence and a similar set of risk and protective factors may underlie depressive symptoms, antisocial behavior, and alcohol use. Analyses test how risk and protective factors for externalizing behavior in community, school, family, peer, and individual domains are related to depressive symptoms, antisocial behavior, and alcohol use concurrently and longitudinally in a sample of 2, 002 students assessed in 8th and 10th grades (52% male; 58% Caucasian). Findings indicate that risk and protective factors for antisocial behavior and alcohol use are also associated with depressive symptoms, both concurrently and longitudinally. Prevention approaches that target risk and protective factors for externalizing problems may have crossover effects on depressive symptoms during adolescence.